Calculation procedure for formulating lauric and palmitic fat blends based on the grouping of triacylglycerol melting points - Nusantoro, Bangun Prajanto; Abdul Manaf, Yanty Noorzianna; Van de Walle, Davy; Hidayat, Chusnul; Danthine, Sabine; Dewettinck, Koen (Consejo Superior de Investigaciones Cientificas, 2017)
A calculation procedure for formulating lauric and palmitic fat blends has been developed based on grouping TAG melting points. This procedure offered more flexibility in choosing the initial fats and oils and eventually gave deeper insight into the existing chemical compositions and better prediction on the physicochemical properties and microstructure of the fat blends. The amount of high, medium and low melting TAGs could be adjusted using the given calculation procedure to obtain the desired functional properties in the fat blends. Solid fat contents and melting behavior of formulated fat blends showed particular patterns with respect to ratio adjustments of the melting TAG groups. These outcomes also suggested that both TAG species and their quantity had a significant influence on the crystallization behavior of the fat blends. Palmitic fat blends, in general, were found to exhibit higher SFC values than those of Lauric fat blends. Instead of the similarity in crystal microstructure, lauric fat blends were stabilized at β polymorph while palmitic fat blends were stabilized at β’ polymorph.